PENYELESAIAN SECARA ADAT TINDAK PIDANA PENIPUAN OLEH NINIK MAMAK TERHADAP TANAH ULAYAT MASYARAKAT DESA SAHILAN DARUSSALAM KECAMATAN GUNUNG SAHILAN - Prabowo, Nugrah; Bachtiar, Maryati; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Land has a very close relationship with humans. The existence of customary rights shows that customary rights have a place and recognition from the State as long as in reality they still exist. The adat community of Gunung Sahilan village, Gunung Sahilan sub-district, Kampar district, is one of the indigenous communities that has a customary land conflict. With regard to the use and management of customary lands in the area of the indigenous communities of Gunung Sahilan village, Gunung Sahilan sub-district, Kampar regency there should be coordination with ninik mamak. but in reality, the role of ninik mamak is no longer applied.The conclusion that can be obtained from the results of the research is First, the Existence of Customary Land in Indigenous Peoples in Kenegerian Sahilan Darussalam Sahilan District, Kampar Regency has begun to fade and slowly began to disappear with the times and civilization. People who intend to open the land must have begun to rarely inform / ask ninik mamak who knows the ins and outs of the land so that customary law is still the main tool in the community. Second, the Settlement of the Land of Ulayat conflicts in Indigenous Peoples in Kenegerian Sahilan Darussalam, Sahilan District, Kampar Regency in general is almost the same between one country and another. The procedure begins with a complaint by the party that feels disadvantaged to the king or the chief either directly or through an intermediary, then the summons of the parties and the final stage of the King / customary judge will conclude what was discussed earlier in the deliberations. and Third, the Obstacles of Ninik mamak in the Malay Customary Institution of the Sahilan Darussalam Village in Resolving the Conflict of Ulayat Land of the Sahilan Darussalam State, among others, consisting of not reaching an agreement between community leaders and PT. RAPP, lack of authority ninik mamak, inaccurate land area and lack of government role.Keywords: Existence, Landslides, Indigenous Peoples, Kenegerian Mount Sahilan